Representations of the Middle School in TV and cinema - Boero, Davide (Rivista di Storia dell’Educazione, 2023)
The essay deals with the history of the Middle School, from its origins up to the present day, through the representation portrayed in media such as movies, news videos, TV programmes - an excellent point of view to discover how public school has been delivered to the general audience. Starting from the pieces preserved in RAI archives and the films available in the Archivio Luce, the text summarises the first representations of the “novelty” brought by a school system different in the pedagogical aims, and outlines the transformations of the following decade, when the delegate Decrees will enrich the debate. To properly summarise the content of the films, the text highlights some recurring subjects and themes, such as the the schooling rate increase and the substantial State investments, the inadequate conditions of school buildings and the lack of educational tools. The second part of the text mainly deals with the new Century, and focuses on documentaries and fiction, to show how movies and TV shows fed on ideas already present to the public, but also substantially contributed to the spreading of the same ideas - magnifying the many common places and prejudices that always labelled the Public School.